Images of Caribbean regional integration : a survey of the perceptions of Caribbean teacher trainees - Grant, Rudolph W. (Ministry of Education, Social Development and Culture GeorgetownGY, 1982)
Focuses on the levels of awareness among Caribbean teacher trainees towards Caribbean regional integration.